The Influence of Brand Image, Brand Trust, Product Quality, and Price on the Consumer’s Buying Decision of MPV Cars - Amron, Amron (European Scientific Journal, ESJ, 2018)
This paper focuses on testing the model of consumer’s buying decision of Multi-Purpose Vehicle (MPV) cars. The research model involved four independent variables of brand image, brand trust, product quality and price; and the dependent variable of buying decision. The study found that the four independent variables were proven to be capable of positively and significantly influencing consumer’s decision in buying MPV cars. However, this study also found that, surprisingly, the variable of prices has the greatest effect compared with the other independent variables influencing consumer’s buying decisions. This study suggested to managements of companies not to only focus their efforts on improving brand image and brand trust from the consumers’ perspective, but to also strive to provide quality products at competitive prices.